The regional space and the world. Rethinking the late viceregal period since the Aguilar y Ubalde conspiracy (1805) - Robles Chinchay, Rubén (2021)
This article explores the way in which various events converge in the origin of the Cuzco separatist conspiracy of Aguilar y Ubalde (1805). With this view, we will seek to recognize how the handling of international information, the tradition and the spaces for dialogue of this early Creole conspiracy, allow us to know more about the situation of the Viceroyalty of Peru in the period prior to the turning point represented by the French invasion. to Spain 1808.